Self-Care Practices and Perspectives in Managing Coronary Heart Disease Patients: A Qualitative Study - Setyowati Setyowati; Aria Wahyuni; Hananto Adriantoro; Kasiyah Junus; Eric Umar; Nelsensius Klau Fauk; Hidayat Arifin (Nursing Reports)
Background/Objectives: Self-care experiences and understanding of coronary heart disease (CHD) play a pivotal role in the management of CHD and can contribute to positive health outcomes. This qualitative study aimed to explore the views and experiences of CHD patients, their families, and Indigenous leaders about self-care practices of CHD. Methods: A qualitative design employing semi-structured interviews and a focus group discussion was used. Employing purposive sampling, 49 respondents, comprising 30 patients, 10 family members, and 9 Indigenous leaders, were recruited and interviewed from April to September 2022. The data were analyzed using content analysis. Results: Five major categories were constructed: (1) inadequate knowledge and early symptom identification; (2) self-care activities for physical, psychosocial, and spiritual needs; (3) family and kinship support for self-care efforts; (4) barriers to self-care including physical, psychological, and access issues; and (5) health improvement expectations based on culturally sensitive health education. Conclusions: The study reveals significant gaps in knowledge about CHD and the identification of early symptoms among patients, families, and Indigenous leaders. Despite efforts to meet physical, psychosocial, and spiritual needs, self-care is hindered by various barriers, including limited access to healthcare and entrenched habits. The support from family and kinship systems is crucial for self-care. Participants expressed a strong desire for culturally tailored health education and better health control to improve heart health outcomes.